A focus group study of students’ expectations of digital onboarding tools in higher education - Schilling, Hannes; Hirschberger, Stephanie; Kauffeld, Simone (Frontiers in Education, 2024)
In higher education, the array of roles performed by digital tools has been increasing rapidly. While some areas of higher education, such as teaching, already employ digital tools, the use of such tools in student onboarding has not yet been thoroughly explored. This study sought to develop a better understanding of student perspectives regarding digital onboarding tools through an investigation that built on the technology acceptance model and expectancy–value theory. The goal was to identify what students expect from digital onboarding tools concerning, for example, content and design. To this end, we examined the data from five focus groups using qualitative content analysis. The results revealed that students expect the design of digital onboarding tools to feature websites that are usable on mobile devices and that such a tool should be readily available for their use independently of time and place. Our study also found that digital onboarding tools can influence students’ motivation to study. The learnings for higher education institutions are that digital onboarding tools should enhance easy information gain and provide opportunities that foster early socialization with fellow students.